Economic impacts of rural tourism development in Kilim Geopark Langkawi - Sapari, Mohamad Safee (Faculty of Economics and Business, UNIMAS, 2012)
Ecotourism in Malaysia has been growing over the las decade and has become a major revenue earner for the country. The government has taken various actions to develop the infrastructure, tourist attraction, businesses and facilities to accommodate the need of tourists. The purpose of this study is to analyze tourist satisfaction towards ecotourism development in Kilim Geoforest Park, Langkawi in terms of environmental, socio-cultural, economic, facilities and services. This study uses tourists’ characteristic approach (socio demographic, information sources, past experiences and motivations) as variable that influence tourists’ satisfaction towards development Kilim Geoforest Park. The study will analyze tourists’ expectation and satisfaction among the tourist as indicated either by positive disconfirmation if the tourists are satisfied or negative disconfirmation if the tourists are not satisfied. The outcome of analysis on tourist satisfaction can produce information, there are useful in management and development of the Kilim Geoforest Park to encourage the tourists to make repeat visit.